Promoting osseointegration of titanium by pH-responsive releasing of H2S and optimizing polarization time for macrophages. (15th March 2023) - Yu, Jinxiu; Gao, Pengfei; Yang, Yulu; Peng, Dan; Zhang, Xianhui; Wang, Danyang; Yang, Weihu; Tang, Yu; Cai, Kaiyong
Abstract: To improve the osteointegration of titanium implant by macrophages immunoregulation, in this study, a functionalized titanium implant was fabricated by storing H2 S donors (JK-1) into Ti nanotubes and plugging with chitosan/gelatin multilayers. After implantation, the inflammation responses were initiated immediately and overlaps with the subsequent regeneration phase. The acidic inflammatory environment could trigger the degradation of multilayers and release of H2 S. By optimizing polarization regulation time of M1 to M2 macrophages, we can maintain the phagocytosis and neovascularization functions of M1 macrophages and improve anti-inflammatory response timely by M2 macrophages polarization. And in turn the immunomodulation of macrophage could lead to the efficient osteogenic differentiation of MSCs. In vivo results showed that keeping M1 macrophages for 2 or 3 days could promote neovascularization around implants. Subsequent M2 macrophages polarization could improve osteogenesis. So, it is a promising strategy for titanium implants improvement was supplied that a better osseointegration of titanium-based implants could be possessed by macrophages immunomodulation.